Religion and Oppression: Analysing ChimamandaNgoziAdichie‟sThe Purple Hibiscus - Abraham, Jolsy (International Journal of Psychosocial Rehabilitation, 2025)
This paper examines how Christianity creates individuals who shun their own traditional beliefs and at the same time oppress those close to them, by drawing analogies between Christianity and Traditional African Religion. Religion is a double edged sword in many ways. It has many positive impacts but has no shortage of negative ones either. Of the plethora of harmful effects it can have, some include rejection or repression of freedom of thought, a communal superiority complex, division within societies and families, loss and removal of critical thought and an opportunity for justification for evil actions. All of these involve oppression inflicted upon, or by the believer. Eugene who is the protagonist of Adichie’sThe Purple Hibiscusloggerheads with his father Papa- Nnukwu whom he calls a heathen because of his beliefs. The oppressive nature of the protagonist towards his fellow beings and the act of violence, strict discipline and aggression suppress the voices of his loved ones and their insurgency.